Characterization of G6PD genotypes and phenotypes on the northwestern Thailand-Myanmar border. - Germana Bancone; Cindy S Chu; Raweewan Somsakchaicharoen; Nongnud Chowwiwat; Daniel M Parker; Prakaykaew Charunwatthana; Nicholas J White; François H Nosten (PLoS ONE, 2014)
Mutations in the glucose-6-phosphate dehydrogenase (G6PD) gene result in red blood cells with increased susceptibility to oxidative damage. Significant haemolysis can be caused by primaquine and other 8-aminoquinoline antimalarials used for the radical treatment of Plasmodium vivax malaria. The distribution and phenotypes of mutations causing G6PD deficiency in the male population of migrants and refugees in a malaria endemic region on the Thailand-Myanmar border were characterized. Blood samples for G6PD fluorescent spot test (FST), G6PD genotyping, and malaria testing were taken from 504 unrelated males of Karen and Burman ethnicities presenting to the outpatient clinics. The overall frequency of G6PD deficiency by the FST was 13.7%. Among the deficient subjects, almost 90% had the Mahidol variant (487G>A) genotype. The remaining subjects had Chinese-4 (392G>T), Viangchan (871G>A), Açores (595A>G), Seattle (844G>C) and Mediterranean (563C>T) variants. Quantification of G6PD activity was performed using a modification of the standard spectrophotometric assay on a subset of 24 samples with Mahidol, Viangchan, Seattle and Chinese-4 mutations; all samples showed a residual enzymatic activity below 10% of normal and were diagnosed correctly by the FST. Further studies are needed to characterise the haemolytic risk of using 8-aminoquinolines in patients with these genotypes.